Interface between regulation and statistics in drug development - Alemayehu, Demissie; Emir, Birol; Gaffney, Michael, active 1983 (Boca Raton : Chapman & Hall/CRC, 2021)
With the critical role of statistics in the design, conduct, analysis and reporting of clinical trials or observational studies intended for regulatory purposes, numerous guidelines have been issued by regulatory authorities around the world focusing on statistical issues related to drug development. However, the available literature on this important topic is sporadic, and often not readily accessible to drug developers or regulatory personnel. This book provides a systematic exposition of the interplay between the two disciplines, including emerging themes pertaining to the acceleration of the development of pharmaceutical medicines to serve patients with unmet needs. Features: Regulatory and statistical interactions throughout the drug development continuum The critical role of the statistician in relation to the changing regulatory and healthcare landscapes Statistical issues that commonly arise in the course of drug development and regulatory interactions Trending topics in drug development, with emphasis on current regulatory thinking and the associated challenges and opportunities The book is designed to be accessible to readers with an intermediate knowledge of statistics, and can be a useful resource to statisticians, medical researchers, and regulatory personnel in drug development, as well as graduate students in the health sciences. The authors' decades of experience in the pharmaceutical industry and academia, and extensive regulatory experience, comes through in the many examples throughout the book.
2.6.4 Challenges with Bayesian Statistics -- 2.6.5 Concluding Remarks -- 2.7 Surrogate Endpoints and Biomarkers -- 2.7.1 Introduction -- 2.7.2 Statistical Considerations -- 2.7.3 Regulatory Considerations -- 2.7.4 Concluding Remarks -- 2.8 Subgroup Analyses -- 2.8.1 Introduction -- 2.8.2 Subgroup Analyses in the Traditional Confirmatory Clinical-Trial Setting -- 2.8.3 Statistical Approaches -- 2.8.4 Reporting and Interpretation of Subgroup Results -- 2.8.5 Subgroup Analyses in the Changing Clinical-Trial and Regulatory Setting -- 2.8.6 Conclusion -- 2.9 Benefit-Risk Assessment
OCLC-licensed vendor bibliographic record.
Keywords: United States. -- Food and Drug Administration -- Rules and practice; Drugs -- United States -- Testing -- Statistical methods; Drugs -- Testing -- Law and legislation -- United States; Clinical trials -- United States -- Statistical methods; Clinical trials -- Law and legislation -- United States; Clinical trials -- Reporting -- United States; Drug development -- United States; Pharmaceutical policy -- United States; MEDICAL / Biostatistics; MATHEMATICS / Probability & Statistics / General; MEDICAL / Pharmacology